Randomized control trial to find the safety and efficacy of the Kiwi OmniCup system in comparison with the conventional vacuum delivery - Mishra, Kalpana; Sarkar, Ruma; Aditya, Vani; Bhadkaria, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Ventouse delivery, also known as vacuum extraction, is a medical procedure employed during childbirth to assist in the safe delivery of a baby when conditions necessitate a quicker or controlled delivery to safeguard the health and well-being of both the baby and the mother. Methods: The research was conducted in the labour room of the Department of Obstetrics and Gynaecology at Baba Raghav das Medical College in Gorakhpur, Uttar Pradesh during September 2019 to August 2020 involve all pregnant women undergoing the process of normal delivery. Thorough maternal histories, physical examinations, and diagnostic tests were conducted and documented. Group A undergoing conventional vacuum extraction and group B utilizing the Kiwi OmniCup. The outcomes of the procedures were meticulously recorded. Results: Instrumental deliveries in both the Ventouse and Kiwi OmniCup groups were primarily conducted due to fetal distress, with 16 cases (40%) and 23 cases (57.5%), respectively. Other medical conditions also contributed to instrumental deliveries, accounting for 16 cases (40%) in the Ventouse group and 9 cases (22.5%) in the Kiwi OmniCup group. Maternal exhaustion led to instrumental deliveries in 8 cases (20%) in both groups. Conclusions: Instrumental deliveries, primarily ventouse and Kiwi OmniCup, were mainly performed due to fetal distress, with ventouse often requiring longer cup application and resulting in more significant blood loss, while Kiwi OmniCup led to neonatal intensive care unit (NICU) admissions primarily due to respiratory distress; however, both methods showed comparable APGAR scores and low rates of severe neonatal complications.